Rate of vision loss in neovascular age-related macular degeneration explored - Real, Juan Pablo (2015)
Purpose: To explore decline in visual acuity in patients with neovascular age-related macular degeneration (n-AMD) awaiting intravitreal bevacizumab or ranibizumab treatment following initial diagnosis and after disease reactivation. Methods: Retrospective analysis of 74 treatment-naïve patients (84 eyes) in two centers in Córdoba, Argentina. The time between treatment indication and intravitreal injection, and the changes in BCVA produced during this delay were studied in both periods. A linear regression model to search the impact of time on progression visual impairment was conducted. Results: In both periods, a significant reduction in vision occurred awaiting intravitreal injection. The longer the delay, the greater the vision loss (R2 = 0.55 p < 0.01) and the less improvement following treatment (Pearson coefficient −0.26). The result of the model shows that the change in vision as a function of initial delay were best described by a polynomic model with a mean loss of 5 letters in the first 3 weeks, a slowdown in the rate of change of VA, and a dependence of visual acuity at the moment of diagnosis. The loss of visual acuity after reactivation shows the same behavior as at the onset of the disease but independent of visual acuity prior to reactivation. Conclusion: Visual loss awaiting injection intravitreal anti-VEGF is clinically significant and with an asymptotic pattern, with early rapid loss of vision in both the onset of the disease and the reactivation. Initiation of anti-VEGF treatment must be undertaken urgently, as should retreatment of disease activation to reduce visual loss.